Volume Changes of Elbrus Glaciers From 1997 to 2017 - Kutuzov, Stanislav; Lavrentiev, Ivan; Smirnov, Andrew; Nosenko, Gennady; Petrakov, Dmitry (Frontiers in Earth Science, 2019)
This study describes the analysis of changes in area and volume of the Mt. Elbrus glacier system, Central Caucasus from 1997 to 2017. It is based on helicopter-borne ice thickness measurements, comparison of high-resolution imagery and two digital elevation models (DEMs) with 10 meter resolution. More than 250 km of ground-penetrating radar (GPR) profiles of ice thickness with reliable reflections were obtained. The total volume of Mt. Elbrus glaciers was 5.03±0.85 km3 of ice in 2017. Our results show that 68% of the total ice volume is concentrated below 4000 m a.s.l. where the average ice thickness was 44.6±7.3 m, 18% of the volume lies within 4000-4500 m a.s.l. (thickness of 41.2±7.3 m), and just 14% lies above 4500 m a.s.l. (thickness of 29.7±6.65 m). The glacier-covered area of Mt. Elbrus decreased from 125.76±0.65 km2 in 1997 to 112.20±0.58 km2 in 2017, a reduction of 10.8%. Over the same period the volume decreased by 22.8%. The mass balance of the Elbrus glaciers decreased by -0.55±0.04 m w.e. a-1 from 1997 to 2017. Mass balance on west-oriented glaciers is less negative than on east-and south-oriented glaciers where mass balance is most negative. The mass balance of the east-oriented Djikiugankez glacier decreased at the fastest average rate (-0.97±0.07 m w.e. a-1). This glacier contains 28% of the total Elbrus glacier system ice volume, most of which is concentrated below 4000 m a.s.l. Only one small glacier on the western slope demonstrated mass gain. Our results match well with the long term direct mass balance measurements on the Garabashi glacier on Elbrus which lost 12.58 m w.e. and 12.92±0.95 m w.e. between 1997 and 2017 estimated by glaciological and geodetic method, respectively. The rate of Elbrus glacier mass loss tripled in 1997-2017 compared with the 1957-1997 period.